Analysis of the Effectiveness and Contribution of Land and Building Taxes to the Original Regional Income of Bekasi Regency - Djatnicka, Erlina; Dian Sulistyorini Wulandari; Khoirun Nisa (Indonesian Journal of Economic & Management Sciences, 2024)
Land and Building Tax (PBB) is one of the regional taxes that has a major contribution to the Regional Original Income (PAD) of Bekasi Regency. This study aims to analyze the level of effectiveness and contribution of land and building tax (PBB) to the regional original income (PAD) of Bekasi Regency. This study used a quantitative descriptive method. The data source used in this study was secondary data with time series data types. Secondary data used are the financial statements of Regional Original Revenue (PAD) revenue and the Bekasi Regency Land and Building Tax (PBB) revenue report for 2017–2019. The results of this study indicate that the effectiveness level of land and building tax (PBB) revenue in Bekasi Regency for three years, namely from 2017 to 2019, shows that the criteria are very effective, with an average achievement of 113%. The contribution rate of land and building tax (PBB) to the regional original income (PAD) of Bekasi Regency for three years, namely from 2017 to 2019, shows the criteria of being deficient with an average of 18%. For the simple regression analysis, the results show that land and building taxes have a positive effect on local revenue